Diễn trình văn hóa tiền sử hang C6-1 qua tư liệu khảo cổ học - Nguyễn, Khắc Sử (2021)
This article introduces the stratigraphic structures, cultural vestiges left by the ancient people, and the absolute dating system of the relics. On that basic, the authors have a few comments on the prehistoric cultural process of cave dwellers and heritage values of C6-1 cave in the context of prehistoric era of Dak Nong in particular and the Central Highlands in general. For the first time, Vietnamese scientists have known a new type of residence, a new adaptation of prehistoric inhabitants in the Central Highlands basaltic soil. The excavation results of the C6-1 cave with thick, intact stratigraphy, C14 dating system, trace of human activies and graves, are a handbook for reference and comparision with prehistoric relics in the Central Highlands. These are also the basic for on-site conservation and promotion of the archaeological cultural heritage for tourism which contributes to socio-economic development in Dak Nong province.